2014
DOI: 10.1002/lpor.201400012
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous brightness enhancement and wavelength conversion to the eye‐safe region in a high‐power diamond Raman laser

Abstract: Brightness enhancement in an external cavity diamond Raman laser designed for high power conversion of a neodymium (1064 nm) laser to the eye‐safe spectral region is reported. Using a multimode input beam pulsed at 36 kHz pulse repetition frequency, 16.2 W with 40% overall conversion efficiency was obtained at the second Stokes wavelength of 1485 nm. The output beam had a quality factor of M2=1.17±0.08 which is a factor of 2.7 times lower than that of the input beam, resulting in a higher overall brightness. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…The technology is now looking very promising for compact high power beam converters. It was recently shown that diamond enables brightness conversion of laser beams, in addition to a wavelength shift [147] . The concept underpinning this is well known and established in the 60-70s in gases, however, it is much more challenging for solid-state converters.…”
Section: Raman Lasersmentioning
confidence: 99%
“…The technology is now looking very promising for compact high power beam converters. It was recently shown that diamond enables brightness conversion of laser beams, in addition to a wavelength shift [147] . The concept underpinning this is well known and established in the 60-70s in gases, however, it is much more challenging for solid-state converters.…”
Section: Raman Lasersmentioning
confidence: 99%
“…In detail, the most interesting advantages of diamond includes the high Raman gain (pumping at 1030 nm, gR = 13.5 ± 2.0 cm/GW) and the large frequency shift of the 1st order Raman mode (1332.5 cm −1 ) [22,48], which could achieve a high-power operation and a sufficient frequency shift. Moreover, the high thermal conductivity (2200 W/m • K), which is two to three orders of magnitude higher than conventional Raman materials, and the low thermal expansion coefficient of diamond (1.1 × 10 −6 K −1 ) will be helpful for power scaling to a high level as well as its high damage threshold [45][46][47][48]. Another important advantage of the diamond is the broad transmission band.…”
Section: Duv Laser Generation Based On Diamond Raman Lasermentioning
confidence: 99%
“…In the past few decades, many Raman materials have been studied [44][45][46], which showed the high conversion efficiency to the first Stokes light from 1 µm. The stimulated Raman scattering (SRS) laser is remarkable for the momentum conservation automatically determined by the scattered phonons, which will induce the Stokes light beam to be a high quality [22,47]. Particularly, by use of the chemical vapor deposition (CVD) diamond, the diamond Raman laser depicted a high power result of 100 W [22] and a high slope efficiency of 84% approaching the quantum limit [23].…”
Section: Duv Laser Generation Based On Diamond Raman Lasermentioning
confidence: 99%
“…This has been seen in a number of materials, but the extreme performance of diamond Raman lasers further enhances this effect. Researchers at Macquarie University have reported improvements in M 2 from pump to Raman beam of a factor of 2.7, whilst converting a pulsed Nd:YAG laser beam from 1064 nm to the eye safe wavelength of 1485 nm [6].…”
Section: Shifting Wavelength Enhancing Brightness With Raman Lasersmentioning
confidence: 99%